LABOR EMPLOYMENT AND UBIKAYU HEALTH REVENUE (Manihot esculenta Crantz) ON HOUSEHOLD FARMS REVENUE - Miftah, Himmatul; Suryana, Dede; Yodfiatfinda, Yodfiatfinda (Universitas Djuanda, 2018)
Increased cassava demand was not followed by an increase in farmer income. To cover the expenditures of households, farmers work in non-agricultural activities. The objective of this research is to analyze the level of household income and contribution of cassava farming to the total income of farm household. The research was conducted in Purabaya Village, Purabaya sub-district, Sukabumi district, conducted from April until June 2013. The location was chosen purposively by Simple Random Sampling of 36 farmers sample. Conclusion The average household income of peani is Rp. 5,721,639 per year or Rp. 476,800 per month. Cassava business income contribution of 59 percent, from non-cassava farming by 9 percent and outside farming ie trade and services 32 percent of total household income Rp 40,553,344, -